2018
DOI: 10.26434/chemrxiv.7301951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering New Defective Phases of UiO Family Metal-Organic Frameworks with Water

Abstract: As defects significantly affect the properties of metal-organic frameworks (MOFs)–from changing their mechanical properties to enhancing their catalytic ability–obtaining synthetic control over defects is essential to tuning the effects on the properties of the MOF. Previous work has shown that synthesis temperature and the identity and concentration of modulating acid are critical factors in determining the nature and distribution of defects in the UiO family of MOFs. In this paper we demonstrate that the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…90,136 Figure 36a presents the PXRD pattern of the samples synthesized with ZrCl4 and shows that the results are in agreement with the reported work. 121 The diffraction pattern for hexagonal nanosheets phase is identical with that of the reported diffraction pattern for hexagonal nanosheets phase. However, the obtained diffraction pattern of hcp phase has few forbidden peaks (Figure 36b).…”
Section: Screening Of Watersupporting
confidence: 81%
See 2 more Smart Citations
“…90,136 Figure 36a presents the PXRD pattern of the samples synthesized with ZrCl4 and shows that the results are in agreement with the reported work. 121 The diffraction pattern for hexagonal nanosheets phase is identical with that of the reported diffraction pattern for hexagonal nanosheets phase. However, the obtained diffraction pattern of hcp phase has few forbidden peaks (Figure 36b).…”
Section: Screening Of Watersupporting
confidence: 81%
“…Further, the PXRD for the samples at 24 h shows that there is a presence of forbidden peaks in the diffraction pattern suggesting the formation of other type of phases(Figure 31). This behavior can be attributed to a small amount of loss of water during the extraction of samples during the course of the experiment, knowing the literature report where water plays an important role in determining phase of MOF material 77,121. In combination, these results led to a systematic screening of amount of water for the synthesis of UiO-67 under concentrated synthesis conditions.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Previous work has demonstrated that the concentration of modulating ligands, such as formate or water, in the reaction mixture dictates the competitive formation of reo and fcu. [4][5][6] Our observations are consistent with local fluctuations in concentration during crystal growth controling the local phase competition. While formate is in substantial excess, terephthalate binds more strongly.…”
Section: Resultssupporting
confidence: 77%
“…The {211} type planes pass through metal clusters and the cluster-ligand attachment sites, which may be linked to the mechanism by which formate modulators compete with terephthalate linkers. [4][5][6] Our multiscale structural analysis shows that defect nanodomains in defect-engineered UiO-66(Hf) exhibit a block-like lamellar morphology and occur in a preferred orientation, extending perpendicular to {111} planes and sometimes perpendicular to other low index facets, with interfaces between reo and fcu domains on {211} planes. These characteristics remain similar across systematically varied defect densities but become more evident at high defect density.…”
Section: Resultsmentioning
confidence: 99%